Mio, my son - Lindgren, Astrid 1907-; Wikland, Ilon. (New York Puffin Books, 1988)
Young Anders is carried away from his bleak life as an unloved foster child in Sweden, to become Mio, the son of the King of Farawayland.
Translation of: Mio, min Mio.
Keywords: Fairy tales